2018
DOI: 10.1002/jgh3.12074
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cut‐off value of fecal calprotectin for the evaluation of ulcerative colitis: An unsolved issue?

Abstract: IntroductionThere is variability in the fecal calprotectin (FCP) cut‐off level for the prediction of ulcerative colitis (UC) disease activity and differentiation from irritable bowel disease (IBS‐D). The FCP cut‐off levels vary from country to country.AimsWe aimed to assess FCP as a marker of disease activity in patients with UC. We determined the optimal FCP cut‐off value for differentiating UC and IBS‐D.MethodsIn a prospective study, we enrolled 76 UC and 30 IBS‐D patients. We studied the correlation of FCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In another study conducted on 76 patients with ulcerative colitis, a sensitivity of 98% and a specificity of 96% at cutoff of 188 μg/g have been reported in this regard [49] ,. In one study, it was shown that fecal calprotectin in cutoff of 127 μg/g is able to distinguish patients with IBD from patients without IBD (patients with diseases other than IBD, patients with IBS, and healthy persons) with 73% sensitivity and 89% specificity [50] ,.…”
Section: The Role Of Fecal Calprotectin In Diagnosis and Management Omentioning
confidence: 84%
“…In another study conducted on 76 patients with ulcerative colitis, a sensitivity of 98% and a specificity of 96% at cutoff of 188 μg/g have been reported in this regard [49] ,. In one study, it was shown that fecal calprotectin in cutoff of 127 μg/g is able to distinguish patients with IBD from patients without IBD (patients with diseases other than IBD, patients with IBS, and healthy persons) with 73% sensitivity and 89% specificity [50] ,.…”
Section: The Role Of Fecal Calprotectin In Diagnosis and Management Omentioning
confidence: 84%
“…The performance of other markers (hemoglobin, CRP, orosomucoid, erythrocyte sedimentation rate, albumins) or the Simple Clinical Colitis Activity Index (SCCAI) as predictors of deep remission and inflammatory activity was not accurate. Jha et al proposed 158 mg/kg for the cut-off value of FC when the definition of mucosal healing was MES ≤ 1 [ 43 ]. Moreover, in a recently published study, Walsh et al showed that FC correlated strongly with UC activity in terms of the endoscopic (UCEIS), histologic (Nancy score), and combined evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…Values of >200 μg/g are also used in daily practice, as a cutoff for additional diagnostics like endoscopy. In IBD, a system of multiple cutoff values has been proposed to differentiate between disease (in) activity (>425 μg/g), mucosal healing (<158 μg/g), and discriminate between IBS and IBD (<188 μg/g) [39]. It seems to be necessary to determine specific RYGB reference values for fCP and lactoferrin if the postoperative elevation is not due to inflammation but, for example, due to altered clearance of the protein.…”
Section: Discussionmentioning
confidence: 99%